The Effectiveness of SETS Learning Model toward the Misconception Decrease of Tenth Graders on Work and Energy Materials (Impulse: Journal of Research and Innovation in Physics Education, 2024)
This study aims to determine the percentage of misconceptions in the work and energy sub-subject and to find out whether the SETS learning model is effective in reducing student misconceptions about work and energy. This research is quantitative research with the type of Pre-Experimental Design using the One Group Pretest-Posttest Design. The sampling technique used in this study was purposive sampling which is a technique for determining samples from members of the population with certain considerations by the desired criteria to be able to determine the number of samples to be studied by taking a sample of class X IPA 2, totaling 30 people. Based on the results of the pretest and posttest, the percentage reduction in misconceptions was 19.14% with an N-Gain of 44% which was included in the medium category. Research data were analyzed by normality test and hypothesis test. The results showed that the normality test using the Shapiro-Wilk test showed that the data were normally distributed with a pretest significance value of 0.842 and a posttest value of 0.520. The results of the research hypothesis using the t-test stated a significance value of 0.000, which means 0.000
Keywords: Misconception; SETS Learning Model; Work and Energy